Health Literacy Level of Nursing Students in The Islamic Colleges of Makassar City - Salsa Bella Fitri Pagesa; Akbar Harisa; Nurhaya Nurdin; Moh. Syafar Sangkala; Silvia Malasari (Faculty of Nursing, Universitas Hasanuddin, 2022)
Introduction. Health literacy is the level of an individual's ability to obtain, process, and understand basic health information and services needed to make appropriate health-related decisions. Nursing students need to understand health literacy in order to prepare themselves to become educative health professionals. Therefore, the researcher intends to conduct research on the level of health literacy of nursing students at the Islamic College of Makassar City. Method. This study uses a quantitative research design with descriptive research methods. The number of samples is 235 people. Result. Analysis of the data found that there was a difference between the level of health literacy between age (p=0.851), gender (p=0.965), semester level (p=0.316), nursing students at Makassar City Colleges. However, there is no significant difference. Conclusion. The need for a compulsory learning program or some kind of special curriculum that discusses health literacy at the academic stage. It is hoped that this related research can to be dug again in depth like finding out what factors which is the cause of universities being found have low health literacy in this study or developed by increasing the number of respondents